Effects of Cardiac Glycosides on Electrical Activity in the Isolated Retina of the Frog - Frank, Robert N. (The Rockefeller University Press, 1967)
Ouabain added to physiological salt solutions bathing the isolated frog retina irreversibly abolishes the electrical response to light (the electroretinogram or ERG). The time course of abolition depends on the concentration of ouabain in the medium and the surface of the retina to which it is applied. When the glycoside is placed on the receptor surface, in 7 min the ERG is completely eliminated by 10(-4) M ouabain and more than 90% inhibited by 3 x 10(-5) M ouabain. The effect is slower at lower concentrations and when the solution is applied to the vitreous surface of the retina. The evidence suggests that abolition of the ERG by ouabain is due principally to inhibition of the active transport of sodium: (a) Structurally modified glycosides which are considerably less potent inhibitors of alkali cation-activated ATPase activity in preparations of frog retinal outer segments are also poorer inhibitors of electrical activity in isolated retinas. (b) Replacing much of the sodium in the medium bathing the retina by choline, Tris, or sucrose significantly protects the retina from ouabain. It is suggested that in a standard sodium environment essentially constant activity of the sodium pump is required to prevent rapid and irreversible change. The cellular sites most critically dependent on the sodium pump have not been identified.